U-2: THE ROLE OF SHAH ABDUL LATIF BHATTAI'S POETRY IN CONTEMPORARY SUFISM AND ITS IMPACT ON SOCIETY: عصر حاضر میں تصوف کی افادیت اور معاشرے پر اس کے اثرات میں شاہ عبد الطیف بھٹائی کی شاعری کا کردار - Begum, Salma (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2022)
Oxford Advance Learner’s Dictionary ‘Mystic a Person who tries to become united With God through prayer and meditation and so understand thing that are beyond normal human understanding. Mysticism: The belief that Knowledge of God and of real truth can be ground through reason and the senses’: Eastern mysticism "A Sufi is a person who seeks to establish a relationship with God, through prayer and meditation, so that he can understand important things that are beyond the comprehension of ordinary human beings." Sufism: The belief that the knowledge of God and the knowledge of true truth can be found through intellect and feelings. It is not possible to give a comprehensive definition of Sufism because Sufism is related to the conditions and places and they change all the time. ۔ In fact, Sufism is the spirit of Islam which has been interpreted as Ihsan in the hadith and the Qur'an has called it "purification". The word Ihsan is used in many places in the Quran: Almighty Allah says: اِنَّ اللّٰهَ مَعَ الَّذِیْنَ اتَّقَوْا وَّ الَّذِیْنَ هُمْ مُّحْسِنُوْنَTranslation: "Allah is with those who guard (against evil) and those who do well." As far as Shah Latif's mysticism is concerned, you are a monotheistic Sufi. All your words are a mirror of Islamic mysticism. The basis of your words is based on mysticism. Be that as it may, you were not only bound by the Shari'ah, but you also set the course for the path, the truth, and the stages of knowledge. All the scholars agree that: Much of Shah's speech is full of subtle points of Sufism. In this article, we will consider how we can bring about change in the society through Shah's speech and bring out the points, which are most needed in the present times.